3D Printed Wearable Apparel Products and Consumer Perceptions (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this article, consumer requirements for clothes printed on a 3D printer are studied. n this, the philosophies of the clothes created by 3D printers of different designers were compared and the theory of offering them to consumers was developed.